Marketing Communication Strategy for Coffee Through Digital Marketing - Nur Alifah; Agus Rohmat Hidayat (Return : Study of Management, Economic and Bussines, 2022)
Background: Marketing communication is one step that has a major influence on the success of a company. Along with the development of technology, the economy, and the market, competition becomes more stringent. For this reason, marketing communication media are needed to be able to reach the target market. For this reason, marketing communication media are needed to be able to reach the target market. Aim: This study aims to explain SCI Coffee's marketing communication strategy, which includes message strategy and media strategy, as implemented through Instagram Method: This research uses a descriptive qualitative method. This research was conducted at the café SCI COFFEE. The population and sample used were all workers at the Syntax Corporation Indonesia office, totaling 100 respondents. Findings: The results of the message strategy research study conducted by SCI via Instagram are information contained in the form of a service model that is close to consumers, offers a place with a comfortable atmosphere, and has a unique café concept that is different in each branch. While the message strategy is through creative message forms in the form of unique photo content and captions. The choice of language for writing captions uses slang. The media strategy carried out by SCI through Instagram as a marketing communication medium, media strategy through target audiences that are tailored to the habits of the target audience, using the current trending Instastory  feature, and the hashtag feature to make it easier for consumers to find places to enjoy good coffee, and election Instagram post time.